Understanding how social support influences peer-delivered HIV prevention interventions among Ugandan female sex workers: a case study from HIV self-testing - McGowan, Maureen; Roche, Stephanie D.; Nakitende, Aidah; Wachinger, Jonas; Nanyiri, Esther; Amongin, Jocelyn; Nakabuye, Ajiri; Musoke, Daniel Kibuuka; McMahon-Rössle, Shannon A.; Bärnighausen, Till; Ortblad, Katrina F. (BMC public health, 2022)
Female sex workers (FSWs) have tightly connected peer networks and remain at high risk of HIV acquisition. Peer delivery of HIV prevention interventions, such as HIV self-testing (HIVST), is a recommended implementation strategy for increasing intervention uptake and continuation among FSWs. We analyzed qualitative data from a peer-delivered HIVST intervention among FSWs in urban Uganda to understand the ways social support within this peer network can motivate or discourage the uptake of peer-delivered HIVST.